Can Thailand achieve COVID‐19 herd immunity? - Manatee Jitanan; Tharisara Chirasatienpon; Rapeeporn Tiamjan; Kwanjai Amnatsatsue; Rachanon Nguanjairak; Adriana Viola Miranda; Xu Lin; Dawa Gyeltshen; Paolo Miguel Manalang Vicerra; M. B. N. Kouwenhoven (Wiley, 2022)
Abstract The COVID‐19 outbreak has had a great impact on the social, economic, and health systems of Thailand. A variety of measures to curb the spread of the disease were implemented since the beginning of the pandemic, including a strict national lockdown protocol. The Thai government aimed to achieve herd immunity through an efficient vaccination programme. Initially, vaccine supply shortage and a lack of vaccine options plagued the health system, but this has since been improved. Continuous monitoring of the situation through research is being carried out to assess the level of immunity among the population whereby the current general recommendation is presently a fourth booster dose for adults. Hurdles towards achieving herd immunity remain. One such issue is the low level of vaccine literacy among those that are unvaccinated or inadequately vaccinated. Another obstacle is the sizeable rate of hesitancy towards getting booster doses. Achieving herd immunity in the Thai population would require multilateral cooperation, improved health promotion to target population groups, such as older adults, and a developed distribution system for those with limited access, such as those in the rural areas.